Potential population impact of the UK government strategy for reducing the burden of coronary heart disease in England: comparing primary and secondary prevention strategies. Issue 5 (30th October 2006) - Gemmell, I; Heller, R F; Payne, K; Edwards, R; Roland, M; Durrington, P
Abstract : Objective: To use population impact measures to help prioritise the National Service Framework (NSF) strategies recommended by the UK government for reducing the population burden of coronary heart disease (CHD). Design: Modelling study. Setting: Primary care. Data sources: Published data on incidence, baseline risk and prevalence of risk factors for CHD and the proportion treated, eligible for treatment, and adhering to the different interventions. Data from meta-analyses and systematic reviews for relative risk and relative risk reduction associated with different risk factors and interventions. Main outcome measures: Population impact measures for the decline in the prevalence of a risk factor and the increased uptake of interventions expressed as number of CHD events prevented in the population. Results: If lifestyle targets for primary prevention are met, 73 522 (95% CI 54 117 to 95 826) CHD events would be prevented per year, with the greatest gain coming from reduced cholesterol and blood pressure levels. In those at high risk of developing CHD, achieving target levels for lifestyle interventions would prevent 4410 (95% CI 1 993 to 8014) CHD events and for pharmacological treatments 2008 (95% CI 790 to 3627) CHD events. For patients with established CHD, achieving NSF targets will result in the prevention of 3067 (95% CI 1572 to 5878) CHD events through improved drug treatment and 1103 (95% CI 179 to 2097) events through lifestyle interventions. Conclusion: Current strategies focus largely on secondary prevention, but many more cardiovascular events would be prevented by meeting the government's public health and primary prevention targets than targeting people at high risk or those with established heart disease.